FAST FOOD CONSUMPTION AMONG ADOLESCENTS AGED BETWEEN (18 TO 25) YEARS OLD AND THEIR EFFECT ON HEALTH IN UZBEKISTAN - Yaxshilikova Aqnur (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Junk meals are wealthy in calories, salt and fats. Excess consumption of junk ingredients would lead upward shove to extensive range of fitness disorders. The motive of this find out about is to discover out about the speedy meals consumption of adolescent in age between 18-25 years old in Navoiy town and their impact on health.Junk ingredients have really carved up the 1/3 World due to globalization; It is an fundamental section of lifestyles in the developed and additionally the creating world, and coming with it is a huge extend in weight problems and associated fitness problems. It grew to be quintessential learn about and decide damaging consequences of junk ingredients consumption and associated problems.